2018
DOI: 10.1158/1055-9965.epi-17-0439
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Overall Survival among Breast Cancer Patients in the U.S. Military Health System

Abstract: Background While research suggests that type 2 diabetes mellitus (DM-2) is associated with overall and breast cancer-specific decreased survival, most prior studies of breast cancer survival investigated the effect of pre-existing DM-2 without assessing the effect of DM-2 diagnosed at or after breast cancer diagnosis. This study examined the relationship between DM-2 diagnosed before and after breast cancer diagnosis and overall survival. Methods This study uses linked Department of Defense cancer registry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…In breast cancer patients with type 2 diabetes mellitus prior to diagnosis, the mortality rate is increased compared to individuals without diabetes (hazard ratio 1.17). The mortality increased further when type 2 diabetes mellitus was diagnosed at or after the breast cancer diagnosis (hazard ratio 1.39) [27].…”
Section: Reviewmentioning
confidence: 99%
“…In breast cancer patients with type 2 diabetes mellitus prior to diagnosis, the mortality rate is increased compared to individuals without diabetes (hazard ratio 1.17). The mortality increased further when type 2 diabetes mellitus was diagnosed at or after the breast cancer diagnosis (hazard ratio 1.39) [27].…”
Section: Reviewmentioning
confidence: 99%
“…Comorbidities at the time of diagnosis may limit treatment options; in addition, the toxicity of cancer treatments is known to cause cardiovascular disease as a late effect, which is why many professional provider organizations have issued guidelines to manage cardiovascular disease in cancer survivors . Data have shown that a diagnosis of diabetes prior to or after a cancer diagnosis increases cancer survivors' mortality . Cardiovascular disease and diabetes are the most common comorbid conditions among cancer survivors, and comorbidities have a negative effect on cancer survivors' long‐term survival .…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders included those measured at cohort entry including, year of cancer diagnosis and age. Co-morbid conditions have been noted to impact upon survival in cancer patients, including breast cancer [ 26 – 28 ], thus our models adjusted for various comorbities (defined at cohort entry) including cerebrovascular disease, chronic pulmonary disease, congestive heart disease, diabetes, liver disease, myocardial infarction, peptic ulcer disease, peripheral vascular disease, renal disease, identified using a list of Read codes modified for use in the CPRD) [ 29 ]. A history of severe mental illness (including schizophrenia-like disorders, bipolar-affective disorders and other non-organic psychoses such as delusional disorder, ‘psychoses not otherwise specified’ and severe depression with psychoses) was identified using Read codes, as used previously [ 1 ].…”
Section: Methodsmentioning
confidence: 99%